Analysis of Thylakoid Membrane Protein Complexes by Blue Native Gel Electrophoresis - Rantala, Marjaana (J Vis Exp, 2018)
Photosynthetic electron transfer chain (ETC) converts solar energy to chemical energy in the form of NADPH and ATP. Four large protein complexes embedded in the thylakoid membrane harvest solar energy to drive electrons from water to NADP(+) via two photosystems, and use the created proton gradient for production of ATP. Photosystem PSII, PSI, cytochrome b(6)f (Cyt b(6)f) and ATPase are all multiprotein complexes with distinct orientation and dynamics in the thylakoid membrane. Valuable information about the composition and interactions of the protein complexes in the thylakoid membrane can be obtained by solubilizing the complexes from the membrane integrity by mild detergents followed by native gel electrophoretic separation of the complexes. Blue native polyacrylamide gel electrophoresis (BN-PAGE) is an analytical method used for the separation of protein complexes in their native and functional form. The method can be used for protein complex purification for more detailed structural analysis, but it also provides a tool to dissect the dynamic interactions between the protein complexes. The method was developed for the analysis of mitochondrial respiratory protein complexes, but has since been optimized and improved for the dissection of the thylakoid protein complexes. Here, we provide a detailed up-to-date protocol for analysis of labile photosynthetic protein complexes and their interactions in Arabidopsis thaliana.